2004
DOI: 10.1016/j.bpc.2004.06.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biochemical and thermodynamic characterization of nucleocapsid protein of SARS

Abstract: The major biochemical and thermodynamic features of nucelocapsid protein of SARS coronavirus (SARS_NP) were characterized by use of non-denatured gel electrophoresis, size-exclusion chromatographic and surface plasmon resonance (SPR) techniques. The results showed that SARS_NP existed in vitro as oligomer, more probably dimer, as the basic functional unit. This protein shows its maximum conformational stability near pH 9.0, and it seems that its oligomer dissociation and protein unfolding occur simultaneously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 35 publications
4
68
0
Order By: Relevance
“…As shown in Figure 1B, the R-galactosidase activity of cells with pGADT7-N and pGBKT7-N is over 2.5 milliunits, which follows the fact that the SARS-CoV N protein could selfassociate as indicated by the published results (16)(17)(18), further confirming that our yeast two-hybrid system is reliable enough. As also indicated in Figure 1B, the ∆N N / ∆N N interaction could not be detected and ∆N C /∆N C showed a stronger interaction than even N/N.…”
Section: Yeast Two-hybrid Technology-based Analysis Of the Interactiosupporting
confidence: 88%
See 2 more Smart Citations
“…As shown in Figure 1B, the R-galactosidase activity of cells with pGADT7-N and pGBKT7-N is over 2.5 milliunits, which follows the fact that the SARS-CoV N protein could selfassociate as indicated by the published results (16)(17)(18), further confirming that our yeast two-hybrid system is reliable enough. As also indicated in Figure 1B, the ∆N N / ∆N N interaction could not be detected and ∆N C /∆N C showed a stronger interaction than even N/N.…”
Section: Yeast Two-hybrid Technology-based Analysis Of the Interactiosupporting
confidence: 88%
“…To compare the multimerization capability of N11 with that of the full-length SARS-CoV N, we applied these two proteins to a gel-filtration column using the same molar concentration. On the basis of the standard proteins as markers ( Figure 5A), the full-length SARS-CoV N protein was found to exist mostly as dimers ( Figure 5B, ---), according to the recently reported results (16,17). However, N11 typically forms multimers as shown in Figure 5B (s).…”
Section: C-terminal 140 Amino Acids (Amino Acids 283-422 N11) Of Sarmentioning
confidence: 79%
See 1 more Smart Citation
“…The C-terminal structural domain coincides with the dimerization domain identified in previous studies, and our biochemical studies showed that it exists as a dimer in solution. Denaturation studies have shown that dissociation of the SARS-CoV N protein is coupled with loss of structure, implying a structure-dependent mechanism for self-association [9]. Understanding this mechanism would not only provide insights into the viral assembly process, but also identify additional targets for drugs to combat SARS through disruption of N protein self-association.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the plasmids for glutathione S-transferase (GST) fusions PGST-ESAT-6 was described previously (Lwabuchi et al, 2004). The recombinant ADAM9 protein of M. tb was cloned, expressed and purified according to the published procedure reported by Luo et al (2004) for GST pull-down assay. For surface plasmon resonance binding assay, ADAM9 was subcloned into pENTR/D-TOPO (Invitrogen) according to the manufacturer's protocol.…”
Section: Plasmids and Construction Of Recombinant Vectorsmentioning
confidence: 99%